Combination lipid-lowering therapy as first-line strategy in very high-risk patients. (12th October 2021) - Ray, Kausik K; Reeskamp, Laurens F; Laufs, Ulrich; Banach, Maciej; Mach, François; Tokgözoğlu, Lale S; Connolly, Derek L; Gerrits, Anja J; Stroes, Erik S G; Masana, Luis; Kastelein, John J P
Graphical Abstract: